PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN (APOTEK K-24 Jl. GADJAH MADA YOGYAKARTA) - Irzaldi Yazid; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2020)
This study aims to analyze the effect of service quality on purchasing decisions Gadjah Mada K-24 Pharmacy, to analyze the effect of prices on purchasing decisions Gadjah Mada K-24 Pharmacy, and to analyze the effect of Service Quality and Price on purchasing decisions at Gadjah M-24 Pharmacy Mada In this study the population in question is the consumer of the Gadjah Mada K-24 Pharmacy. This population is infinite in number so action is needed in sampling for research. The sample in this study were consumers of the K-24 Gadjah Mada Pharmacy as many as 100 respondents. Sampling of 100 refers to Cooper and Emory's theory which assumes that the population is infinite. The sampling technique in this study uses Nonprobability Sampling with purposive sampling and accidental sampling techniques. The conclusion of this study is the quality of service at Gadjah Mada K-24 Pharmacy No. 40 Yogyakarta has been classified as good, the price at Gadjah Mada K-24 Pharmacy No. 40 Yogyakarta has been classified as good, the Purchasing Decision at Gadjah Mada K-24 Pharmacy No. 40 Yogyakarta has been classified as fine good, service quality has a negative relationship, and service quality and price variables not significaton to the decision variable